HNRNPH1 Is a Novel Regulator Of Cellular Proliferation and Disease Progression in Chronic Myeloid Leukemia - Liu, Menghan; Yang, Lin; Liu, Xiaojun; Nie, Ziyuan; Zhang, Xiaoyan; Lu, Yaqiong; Pan, Yuxia; Wang, Xingzhe; Luo, Jianmin (Frontiers in Oncology, 2021)
RNA binding proteins act as essential modulators in cancers by regulating biological cellular processes. Heterogeneous nuclear ribonucleoprotein H1 (HNRNPH1), as a key member of the heterogeneous nuclear ribonucleoproteins family, is frequently upregulated in multiple cancer cells and involved in tumorigenesis. However, the function of HNRNPH1 in chronic myeloid leukemia (CML) remains unclear. In the present study, we revealed that HNRNPH1 expression level was upregulated in CML patients and cell lines. Moreover, the higher level of HNRNPH1 was correlated with disease progression of CML. In vivo and vitro experiments showed that knockdown of HNRNPH1 inhibited cell proliferation and promoted cell apoptosis in CML cells. Importantly, knockdown of HNRNPH1 in CML cells enhanced sensitivity to imatinib. Mechanically, HNRNPH1 could bind to the mRNA of PTPN6 and negatively regulated its expression. PTPN6 mediated the regulation between HNRNPH1 and PI3K/AKT activation. Furthermore, the HNRNPH1-PTPN6-PI3K/AKT axis played a critical role in CML tumorigenesis and development. The present study first investigated the deregulated HNRNPH1-PTPN6-PI3K/AKT axis moderated cell growth and apoptosis in CML cells, targeting this pathway may be a therapeutic CML treatment.